A Study on Perception of Male Adolescents on Sexual Harassment in Higher Secondary Schools of Bhaktapur District - Prajapati, N (2016)
Background: Sexual harassment is defined as unwelcome sexual advances, requests for sexual favors and other verbal or physical conduct of sexual nature. It is hard to identify the sexual harassment as the way in which the victim perceives defines it. Male are usually involved in as well as accused for sexual harassment while there are instances when male are also harassed. Sexual harassment is complex and hard to define and is outcome of varying level of perception about gender roles and power distribution in the society. The study mainly aimed to explore the perception of male adolescents on sexual harassment. Methods: A descriptive cross sectional study was applied to study the perception of male adolescents on sexual harassment involving 202 male adolescents studying in grade 11 and 12 in 8 different higher secondary schools in Bhaktapur District using a semi-structured, self administered questionnaire. Results: Male adolescents easily understood direct and suggestive physical behaviour as sexual harassment but a very few perceived verbal and non verbal behaviour as sexual harassment. But only, 10% of the male adolescents had good perception of physical form of sexual harassment, similarly, only 4% and 2% had good perception of verbal and non-verbal sexual harassment. 83% of the male adolescents perceived the way a girl dresses as the reason for her sexual harassment The that study found 49% of male adolescents have gender inequitable perception which is significantly associated with perception of sexual harassment (p = 0.00). Sexual harassment is usually the manifestation of complex mix of patriarchal practices, gender based violence and ongoing women and sexual violence in societies of Nepal. Deeply rooted gender beliefs and norms are responsible factors that influence the perception regarding sexual harassment.